Clima Organizacional en una Empresa De Obra Civil (2024)
Introduction The theory of human relations was spread in Europe and North America, this theory considers man as a social being, with fears, feelings and desires; thus describing the behavior of the collaborator as a consequence of many motivational factors (1); this theory was widely used in the United States industry, because the benefits obtained in its application were evidenced, in November 1924 one of the most important telephone equipment manufacturing companies in the United States, called Western Electric Co, began the study of a series of "experiments aimed at measuring the influence of lighting conditions on the worker's productivity curve" (2), this gave rise to the Humanistic School of Management, which was developed by the sociologist and psychologist Elton Mayo (1). Objective To describe the organizational climate in a civil works company Methodology A project was carried out by applying the organizational climate questionnaire